Perencanaan Perawatan Mesin Building Dengan Metode Reliability Centered Maintenance (RCM) - Muhazir, Achmad; Sinaga, Zulkani; Septiadi, Resky Dwi (Jurnal Optimalisasi, 2024)
PT. Bridgestone Tire Indonesia is a tire manufacturing company. Machines that work continuously and lack of stock availability of machine spare parts cause damage and increase maintenance costs. To reduce the occurrence of damage and increase maintenance costs, it is necessary to have an optimal maintenance policy so that the machine can operate well. To overcome the problems in this research using the Reliability Centered Maintenance (RCM) method, the first step is determining the critical components on the machine, preparing the FMEA table based on the function data of the components and maintenance reports and calculating the Risk Priority Number (RPN), then calculating the MTTF and MTTR to determine maintenance and repair intervals and find optimal total maintenance costs. Machine building has the highest frequency of downtime so this research will focus on machine building components. The results of data processing show that the highest frequency of machine damage and total downtime is the cause of hose component failure due to poor hose quality and seal components becoming worn, causing increased frequency of damage, downtime and maintenance costs. Based on maintenance cost calculations using the RCM method, hose and seal components experienced a decrease in costs, namely hose components by 55.13% and seal components by 25.45%. The proposed building machine maintenance for hose and seal components in particular is to carry out scheduled tasks, scheduled exhaust tasks, and default actions with the task category of finding failures and results for maintenance time intervals for hose components of 280.81 hours and for seal components of 134.08 hours.